Formulation of Polyethylene Glycol Based Ibuprofen Nanosuppository Preparations and Assesment of Dissolution - Dewi Fitriani Puspitasari; Yani Kresnawati (Jurnal Kesehatan dr. Soebandi, 2024)
Ibuprofen is widely formulated in oral and rectal dosage forms. Ibuprofen in the rectal route shows c max and t max longer than syrup preparations, this is due to the low solubility of ibuprofen. Nanoparticles are one of the technologies that are widely used to increase the solubility of an active substance. Nanoscale particle size, can increase the solubility of ibuprofen and allow dose reduction. This study aims to formulate ibuprofen nanosuppository preparations, and test the percent dissolution of nanosuppositories compared to conventional suppositories. The ibuprofen nanosuppository formulation consists of ibuprofen lipid component and PEG mix component (PEG 4000: PEG 6000). The ibuprofen lipid component consisted of ibuprofen VCO oil, tween 80 and propylenglycol. This lipid component was then tested for physical characteristics, transmittance, particle size and zeta potential, then the lipid was added to the suppository base component. The responses observed were disintegration time, hardness, and non-intrinsic dissolution efficiency. The test results showed transmittance values of 91.98%, 92.99%, 93.26%. Particle size and potential zeta values of FI = 107, 5 nm, FII 102 nm and FIII 103 nm. The zeta potential were -16.19 mV, -12.44 and -13.25 mV in the lipid component. The test results of the disintegration time of F1, F2, F3 nanosuppositories were 12 minutes, 11 minutes and 10 minutes. The hardness of F1, F2, and F3 were 1.53 kg, 1.43 kg and 1.26 kg and the dissolution efficiency value was higher than conventional suppositories. Modification of ibuprofen nanosuppositories had a significant effect on the percent dissolution of ibuprofen.